The association between platelet-to-albumin ratio and diabetic peripheral neuropathy: A cross-sectional study in the Chinese population - Wenting Deng; Siqi Zhang; Yueyang Zhang; Qin Wan (PLoS ONE, 2026)
Introduction The early prevention and diagnosis of diabetic complications are challenging, particularly for diabetic peripheral neuropathy (DPN), which progresses insidiously and irreversibly. Currently, reliable biomarkers associated with DPN are still limited. This study explored the association between the platelet-to-albumin ratio (PAR) and diabetic peripheral neuropathy in Chinese adults with type 2 diabetes mellitus(T2DM). Methods This cross-sectional study included adult patients with T2DM enrolled in the metabolic management center (MMC) database at the Affiliated Hospital of Southwest Medical University between June 2018 and December 2023. Participants meeting the predefined eligibility criteria were classified into diabetic peripheral neuropathy (DPN) and non-diabetic peripheral neuropathy (non-DPN) groups. The association between PAR and DPN was evaluated using logistic regression models, with subgroup analyses and restricted cubic spline regression used to examine potential effect modification and dose–response relationships. Receiver operating characteristic (ROC) curve analysis was performed to assess the discriminative ability of PAR for identifying DPN. Results Among 1,141 patients with T2DM, including 427 patients with DPN, PAR levels were significantly higher in the DPN group than in the non-DPN group ( P < 0.001). Univariate analysis showed that higher PAR (OR=1.282, 95% CI: 1.183–1.389, P < 0.001) significantly increased the prevalence of DPN. After adjusting for confounders, the platelet-to-albumin ratio (PAR) remained independently associated with DPN (OR = 1.158, 95% CI: 1.0511.276, P = 0.003). In subgroup analysis, no significant interaction was observed (all P for interaction > 0.05). The restricted cubic spline regression confirmed a positive linear association between PAR levels and DPN ( P = 0.001, P for nonlinearity = 0.986). Additionally, ROC analysis identified an optimal PAR cut-off value of 5.5971 for distinguishing patients with and without DPN. Conclusions In patients with T2DM, higher platelet-to-albumin ratio(PAR) levels were associated with the prevalence of diabetic peripheral neuropathy. This association may be related to underlying inflammatory processes involved in DPN.